Struggling for Self-Reliance: Four case studies of Australian Regional Force Projection in the late 1980s and the 1990s - Green, Bob (Canberra Papers on Strategy and Defence, 2008)
Military force projection is the self-reliant capacity to strike from mainland ports, bases and airfields to protect Australia's sovereignty as well as more distant national interests. Force projection is not just a flex of military muscle in times of emergency or the act of dispatching forces. It is a cycle of force preparation, command, deployment, protection, employment, sustainment, rotation, redeployment and reconstitution. If the Australian Defence Force consistently gets this cycle wrong, then there is something wrong with Australia's defence. This monograph is a force projection audit of four Australian regional force projections in the late 1980s and the 1990s-valid measures of competence. It concludes that Australia is running out of luck and time. The Rudd Government has commissioned a new Defence White paper. This monograph is Exhibit A for change